2020
DOI: 10.3390/vetsci7040181
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Honey Samples from Ukraine

Abstract: The employment of natural substances such as beehive products with a preventive and therapeutic purpose has been a widespread custom since ancient times. In this investigation, the antibacterial activity of 41 honey samples from different Ukraine regions has been evaluated. For each honey, melissopalynological and physico-chemical analysis were performed in order to determine botanical origin, pH, glucose and fructose contents and free acidity. So, antibacterial activity against Staphylococcusaureus CCM 4223, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…However, glucose concentration was not too much higher (26 %) as shown in Table 3 . Higher concentration of fructose may contribute in the higher antibacterial property of the honey ( Yuksel, 2011 , Oryan et al, 2016 , Cilia et al, 2020 ). Production of hydrogen peroxide by glucose oxidase from glucose may be another reason of the antibacterial potential of the honey ( Sagona et al, 2015 , Cilia et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, glucose concentration was not too much higher (26 %) as shown in Table 3 . Higher concentration of fructose may contribute in the higher antibacterial property of the honey ( Yuksel, 2011 , Oryan et al, 2016 , Cilia et al, 2020 ). Production of hydrogen peroxide by glucose oxidase from glucose may be another reason of the antibacterial potential of the honey ( Sagona et al, 2015 , Cilia et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Higher concentration of fructose may contribute in the higher antibacterial property of the honey ( Yuksel, 2011 , Oryan et al, 2016 , Cilia et al, 2020 ). Production of hydrogen peroxide by glucose oxidase from glucose may be another reason of the antibacterial potential of the honey ( Sagona et al, 2015 , Cilia et al, 2020 ). In our study, reasonable proportions of fructose and glucose may thus cumulatively contribute towards the antibacterial efficacy of honey produced by A. dorsata .…”
Section: Resultsmentioning
confidence: 99%
“…The biological (antimicrobial, antioxidant) and nutritional properties of BCP and BB are directly related to their composition, which in turn is directly related to their botanical origin [ 53 , 54 ]. This is the case for other bee products such as honey or even beeswax [ 55 , 56 , 57 , 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the antibacterial and antimicrobial activity of honey is related to the inhibition of microbial growth throughout different processes [39]. One process is associated to the enzymatic action, namely hydrogen peroxide (H 2 O 2 ), and the other is related to the action of different compounds, such as the high content of sugars, viscosity, osmotic pressure and low pH [26], water activity or protein content [106,144]. In addition, polyphenols, phenolic acids, flavonoids, together with antioxidants, lysozyme, methylglyoxal, and bee peptides (especially the peptide Defensin-1) [134,145] are other vital components of this property.…”
Section: Antibacterial Effectsmentioning
confidence: 99%
“…Studies that have evaluated the antibacterial potential of honey showed that the bioactive compounds found in honey's composition manifest in a direct correlation with the antimicrobial effects of honey [73,156,157]. Therefore, the antibacterial activity of honey may vary according to the geographical and botanical origin of the raw material [158][159][160], as the content of polyphenols can influence its beneficial health effects [144]. Literature reports that phenolic compounds have a well-structured antibacterial mechanism [28], as they are capable to diminish antibiotic resistance of infective bacteria and to prevent biofilm formation [161].…”
Section: Antibacterial Effectsmentioning
confidence: 99%